Effects of Aluminium on Long‐Term Memory in Rats and on SIRT1 Mediating the Transcription of CREB‐Dependent Gene in Hippocampus. Issue 4 (19th June 2017) - Yan, Dongying; Jin, Cuihong; Cao, Yang; Wang, Lulu; Lu, Xiaobo; Yang, Jinghua; Wu, Shengwen; Cai, Yuan
Abstract: Epidemiological investigations have shown that aluminium (Al) is an important neurotoxicant which can be absorbed by organisms via various routes. Previous studies have confirmed that exposure to Al could cause neurodegenerative diseases, decline CREB phosphorylation and then down‐regulate the transcription and protein expression of its target genes including BDNF. However, recent studies revealed that CREB activation alone was far from enough to activate the expression of long‐term memory (LTM)‐related genes; there might be other regulatory factors involved in this process. Several studies showed that TORC1 might be involved in regulating the transcription of downstream target genes as well. Also, TORC1 could be mediated by SIRT1 during the formation of LTM. However, the role of CREB regulating system in Al‐induced LTM impairment was still not utterly elucidated till now. This study was designed to establish the rat model of subchronic Al exposure to observe the neuroethology, regulatory factor levels and molecular biological alterations in hippocampal cells. The results showed that, with the increasing AlCl3 dose, blood Al content increased gradually; morphology of the hippocampus and neuronal ultrastructure were aberrant; in the Morris water maze test, the escape latency and distance travelled became longer, swimming traces turned more complicated in the place navigation test; intracellular Ca 2+, cAMP levels declined significantly in AlCl3 ‐treated rats, followed by abated nuclear translocation of TORC1 and decreased SIRT1, TORC1 and pCREB levels. These results indicate that SIRT1 and TORC1 might play an important mediating role in Al‐induced LTM impairment.